Early female germline development in Xenopus laevis : Stem cells, nurse cells, and germline cysts - Asya Davidian; Allan C. Spradling (Proceedings of the National Academy of Sciences, 2025)
In Drosophila, germline cysts arise through synchronous mitotic divisions and acquire a polarized architecture organized by the fusome, which guides oocyte specification and supports meiotic progression. Similar cyst structures exist in nonmammalian vertebrate ovaries, but their polarity and function have remained uncertain. Using single-cell RNA sequencing and high-resolution imaging, we reconstructed the germ cell differentiation trajectory in Xenopus laevis and uncovered striking parallels with invertebrate and mouse cyst development. We identified a distinct germline stem cell (GSC) population marked by piwil4 , low translational activity, and expression of neuronal-specific and transposon-silencing genes. Downstream from GSCs, during cyst development, an asymmetric fusome-like structure composed of stable microtubules forms a rosette-like connection between cystocytes and contains Golgi vesicles and endoplasmic reticulum, suggesting polarized trafficking. In contrast to previous claims, ~80% of cyst cells turned over rather than forming oocytes, consistent with a nurse cell fate. The striking parallels described here between cyst and fusome formation, polarization, cyst breakdown, and nurse-like cell turnover to produce relatively few oocytes argue that amphibian cysts have important functions in female gametogenesis.